Singing sleuth : three romantic mysteries - McCall, Stephanie Cassandra (2010)
The novella collection Singing Sleuth: Three Romantic Mysteries is a vital contribution to the creative arts because it fills an artistic gap. Within creative writing, a myriad of romantic stories and police procedurals exist. However, although genre-blending has become popular, it is rare that the romance and the detective story get blended in one plot, let alone three that center on the same protagonist. However, there are many readers who appreciate a bit of romance within a gritty mystery, or vice versa, that the collection does fill a need for. What is even rarer is a story or collection that cements these two genres and also incorporates a spiritual thread. Singing Sleuth does this not only in its dialogue and characters, but in the restraint it uses. For example, unlike in secular romances, there is no sexual activity except between married couples, and even then, it is discreetly handled. Also, unlike secular mysteries or thrillers, the collection?s violence is not gratuitous or graphic. Therefore, the collection serves a special purpose for a religious audience by giving them an entertaining read without the pitfalls of action they would rather not read about. In order to write the novella collection, I conducted different types of creative research. Most of this research involved reading inspirational romance and mystery novels, as well as some novella anthologies already on the market that blend the two genres. I also took time to polish my craft in general, using books on plot, structure, and other elements to sharpen my writing. Finally, I was fortunate to be given the contact information for a retired Chicago police officer, who proved a valuable resource because my heroine is a homicide detective. Personal experience also played a major role—having been in theater and choirs for many years, I was able to write the many performing arts scenes with authenticity. As a result of my research, I was able to create a full and well-developed novella collection that seamlessly blended two opposing genres. I was also able to stretch my writing skills because until this project, I had never written a mystery and only attempted romance. The project required learning many new things, such as how law enforcement works, the complexities of romantic relationships, and how I could grow and mature as a writer. I believe the implications raised by my project are myriad. First, the existence of such a collection confirms that the genre blend of romance and police procedural can exist. Because the elements of these genres will also draw in readers despite, or perhaps because of, a spiritual thread, the implication also exists that spirituality can be entertaining and creative. However, I think the most serious implication the collection raises is that creativity knows no borders. Others have asked if such a unique collection is publishable. I believe it is, and furthermore, I believe a story like mine will help the writing world to open itself up to even more unconventional projects.